Biochemical characterization of crude extract from Pleuroncodes planipes (Crustacea: Galatheidae) as potential feed additive, considerations for a new fishery along the Mexico Pacific coast - Vega-Villasante, Fernando; Nolasco, Héctor; Fallarero, Adyary; Carrillo-Farnes, Olimpia (HIDROBIOLÓGICA, 2017)
The red crab Pleuroncodes planipes, commonly called "langostilla" is arguably the most abundant benthonic decapod of west coast Mexico, with natural productivity estimated at 735,000 metric tons/year. At the present time, it has not been exploited commercially. The implementation of a new fishery in Mexico, based on the capture of red carb, offers diversification of the fishing industry. In this work, a raw extract of langostilla, obtained by mechanical pressing of the whole organism, was analyzed as a potential feed ingredient or additive for cultured marine species. The lyophilized red crab extracts possessed: 1) enzymatic activity of protease, trypsin, amylase, and lipase; 2) no inhibition of serine-proteases; 3) antioxidant capacity against lipoperoxidation and superoxide ions produced by xanthine oxidase reaction; and 4) activity of insulin-like peptides. The amino acid profile shows high levels of arginine, lysine, and methionine. The cheical score of extract protein was compared with M. japonicus larvae, whole body fish tissue, and short-necked clam tissue. The digestibility of the product was 95% taking purified casein as reference. These biochemical and nutritional characteristics are discussed. These results offer a new use of red crab and the potential of a new fishery in Mexico.